2018
DOI: 10.1111/jorc.12239
|View full text |Cite
|
Sign up to set email alerts
|

Tracking patients with advanced kidney disease in the last 12 months of life

Abstract: We found a substantial symptom burden and slow functional decline in this group of patients. Regular assessment of both symptoms and QOL is warranted particularly if clinical experience indicates that the person is likely to be in their last year of life. Integrated supportive care programmes could assist with easing symptom burden during this time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
3
3
1
Order By: Relevance
“…The results of the survey (HEM preday : 0.82 ± 0.94, HEM day : 0.95 ± 0.83, and HEM postday : 1.41 ± 1.82, km/day) are not in line with those of Brown et al [ 7 ] who reported a decrease in patients' physical activity after hemodialysis. However, the findings of the research are in line with those of Bonner et al [ 13 ] who showed the strong influence of the disease on work, daily life, and in general the lifestyle of patients while at the same time identifying differences between them due to their different lifestyles.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The results of the survey (HEM preday : 0.82 ± 0.94, HEM day : 0.95 ± 0.83, and HEM postday : 1.41 ± 1.82, km/day) are not in line with those of Brown et al [ 7 ] who reported a decrease in patients' physical activity after hemodialysis. However, the findings of the research are in line with those of Bonner et al [ 13 ] who showed the strong influence of the disease on work, daily life, and in general the lifestyle of patients while at the same time identifying differences between them due to their different lifestyles.…”
Section: Discussionsupporting
confidence: 89%
“…Concerns about the physical health and dependence of the artificial kidney machine cause severe symptoms of anxiety and depression in patients undergoing dialysis following the onset of mental disorders. Significant mental disorders identified are phobias and coercion in the therapeutic approach, while social disorders are not uncommon [13]. The change in appearance and the self-esteem decline that accompany it lead to introversion and isolation, and relationships with the social environment are affected.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the most common symptoms among participants with ESRD were pain, lack of energy, numbness, itching, and difficulty sleeping. This was slightly different from what has been previously reported [ 10 , 12 , 23 , 24 ]. For example, in a study conducted in Saudi Arabia, Almutary et al [ 10 ] found that the most prevalent symptoms among patients with ESRD were fatigue, bone pain, itching, and decreased appetite.…”
Section: Discussioncontrasting
confidence: 99%
“…Multiple studies have been conducted to assess the prevalence of symptoms among patients with chronic obstructive pulmonary disease (COPD), chronic heart failure (CHF), and end-stage renal disease (ESRD) [ 9 12 ]. For example, a study was conducted to assess the burden of symptoms among COPD patients and found that patients experienced on average 13 to 15 symptoms [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent to some extent with, Bonner et al . (), who reported that, regardless of the treatment modality (i.e. dialysis or conservative management), those who were potentially in their last 12 months of life had relatively stable HRQoL over time.…”
Section: Discussionmentioning
confidence: 99%